Corporate Social Responsibility and Employee Attraction, Motivation and Retention in Nepalese Commercial Banks - Shrestha, Rohit Kumar; Dhakal, Bhakta Prasad (Patan Prospective Journal, 2023)
This study attempts to assess the influence of employee-related corporate social responsibility initiatives on employee attraction, motivation, and retention in Nepalese commercial banking sectors. The study adopted a causal-comparative research design. This study used a quantitative approach. Nepal Bank Limited, Rashtriya Banijya Bank Limited, Himalayan Bank Limited, and Century Commercial Bank Limited were selected as sample units. The study was conducted based on primary data to be collected. These banks have a total of 1134 employees working in several hierarchies and positions. The study was performed by including a structured survey-based questionnaire on a sample of 340 employees who answered the questionnaire using a five-point Likert scale instrument. Descriptive and inferential statistics were used for data analysis. Means and Standard Deviation indicate a positive association between them.A moderate correlation was found between corporate social responsibility toward employees and employee attraction, motivation, and retention. The correlation between customer factors and employee attraction, motivation, and retention was also found moderate. Similarly, a moderate correlation was found between corporate social responsibility to the environment and employee attraction, motivation, and retention. Regression analysis indicates that employee-related corporate social responsibility, customer[1]related corporate social responsibility, and environment-related corporate social responsibility have a positive, moderate, and significant impact on employee attraction, motivation, and retention. It is concluded that independent variables moderately enhance employee attraction, motivation, and retention. Banks should spend money on employee-related corporate social responsibilityactivities like compensation and motivational factors. Future research could focus on the industries such as hospitality and insurance industries.